2006
DOI: 10.2332/allergolint.55.343
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Cutaneous Allergic Vasculitis: A Case Report

Abstract: Mast cells may increase in the skin lesion of cutaneous allergic vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, tryptase may play an important role in the pathogenesis of the Koebner phenomenon. [9] Although not extensively studied in vasculitis, recent studies showed that immuno-enzyme-histological staining of tryptase (a marker for mast cell activation) was found in cutaneous allergic vasculitis[10] or HSP nephritis. [11]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tryptase may play an important role in the pathogenesis of the Koebner phenomenon. [9] Although not extensively studied in vasculitis, recent studies showed that immuno-enzyme-histological staining of tryptase (a marker for mast cell activation) was found in cutaneous allergic vasculitis[10] or HSP nephritis. [11]…”
Section: Discussionmentioning
confidence: 99%
“…In conditions such as leukocytoclastic vasculitis, activated MCs contribute to enhancing vascular permeability and facilitating the migration of leukocytes. An increased perivascular presence of MCs has been demonstrated in skin lesions characteristic of cutaneous allergic vasculitis and in urticarial vasculitis associated with systemic sclerosis 50 , 51 .…”
Section: Mast Cellsmentioning
confidence: 99%
“…The results are expressed as the mean ± SD. The ratios Chy act /Chy prot and Chy act /Try prot were calculated from each individual value * p = 0.029 when PP was compared with IP Previously, one case study [13] has examined mast cell tryptase in leukocytoclastic vasculitis. This study reported high numbers of tryptase ?…”
Section: Correlation Between Mast Cell Proteinases and Immunofluorescmentioning
confidence: 99%
“…Tryptase and chymase are the major proteins in MC TC mast cells and, therefore, they can have profound effects whenever released upon mast cell activation in vasculitis. Although mast cell tryptase and chymase have been studied in many different skin diseases [4,10], only very limited information on them is available in human cutaneous vasculitis [13]. In some older publications, mast cells have been examined in cutaneous vasculitis, but the reports deal with mast cell degranulation [23,26].…”
Section: Introductionmentioning
confidence: 99%